Rice residue management on Fadama lands and their effects on soil properties and crop development - Abdullahi, Abubakar Sadiq; Ahmad, Desa; Amin, Sunusi Abubakar (School of Social Sciences, Universiti Sains Malaysia, 2012)
Rice hulls / husks were used as a stubble material to investigate their effects on soil properties root and shoot development of maize. Soils were sampled from five Fadama fields in Bauchi State, Nigeria. Under varied compaction (0 - 8 blows) and hulls levels (0 – 400 g), the soil bulk density was found to decrease from 2.01 to 1.23 g/cm3. Under screen house test, the maize root and shoot are also influenced by number of blows (compaction) and hulls level added. At seven and fourteen days after germination (DAG), longest root development of 10 and 16 cm and shoot length of 19.3 and 36.0 cm were recorded for 200 g hulls added and at 4 compaction blows. Use of rice hulls on farms will improve soil properties due to machinery traffic and prevent pollution of environments.